2022
DOI: 10.3390/ijms23084450
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis KCS5 and KCS6 Play Redundant Roles in Wax Synthesis

Abstract: 3-ketoacyl-CoA synthases (KCSs), as components of a fatty acid elongase (FAE) complex, play key roles in determining the chain length of very-long-chain fatty acids (VLCFAs). KCS6, taking a predominate role during the elongation from C26 to C28, is well known to play an important role in wax synthesis. KCS5 is one paralog of KCS6 and its role in wax synthesis remains unknown. Wax phenotype analysis showed that in kcs5 mutants, the total amounts of wax components derived from carbon 32 (C32) and C34 were appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 56 publications
3
29
2
Order By: Relevance
“…(5) Subcellular localization analysis showed that the BrCER60.A09was localized to the ER, which is the site of wax biosynthesis. (6) Cuticular wax composition analysis showed a reduction of wax monomers with chain lengths beyond C26 and an increased proportion of shorter chains, which was in agreement with the CER60 function in Arabidopsis (Huang et al 2022). Overall, the 5,567-bp insertion of BrCER60.A09 in SD369 was the main cause of the glossy phenotype.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…(5) Subcellular localization analysis showed that the BrCER60.A09was localized to the ER, which is the site of wax biosynthesis. (6) Cuticular wax composition analysis showed a reduction of wax monomers with chain lengths beyond C26 and an increased proportion of shorter chains, which was in agreement with the CER60 function in Arabidopsis (Huang et al 2022). Overall, the 5,567-bp insertion of BrCER60.A09 in SD369 was the main cause of the glossy phenotype.…”
Section: Discussionsupporting
confidence: 70%
“…The cer6 mutant showed a substantial reduction of derivatives beyond C26, and nearly abolished stem wax accumulation, and exhibited conditional male sterility (Fiebig et al 2000;Hooker et al 2002;Huang et al 2022;Millar et al 1999). CER60/KCS5, a paralog of CER6/KCS6, play a redundant role with CER6/KCS6 in wax biosynthesis, but CER6/KCS6 plays a major role (Huang et al 2022). The mutation in CER60/KCS5 caused only a slight reduction in total wax amounts in leaves and owers, and the wax amounts in stems barely changed (Huang et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Bacillus spp. and its products have been shown to stimulate the plant immune response and induce systemic resistance (ISR) and upregulate the pathogenicity-related genes in plants [ 55 , 56 ]. The rapid buildup of H 2 O 2 is considered to be a significant phytopathogen defense signal in cellular plants [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the wake of climate change, drought has become a calamitous abiotic stress, affecting plant growth and hampering agricultural production and yield. The economic impact of this stress is likely to increase further; as a result, there has been growing interest in studying drought stress responses and tolerance mechanisms of natural drought-tolerant plants [48], such as Ziziphus nummularia. The purpose will be to develop crops with increased tolerance and resilience to drought.…”
Section: Anti-drought and Anti-thermal Characteristics Of Ziziphus Nu...mentioning
confidence: 99%